New oral anticoagulants in development - Weitz, Jeffrey I. (Thrombosis and Haemostasis, 2010)
Although currently available anticoagulants are effective for the prevention and treatment of thromboembolic disorders, they have several drawbacks. Low-molecular-weight heparins and fondaparinux produce a predictable level of anticoagulation that obviates the need for coagulation monitoring, but they must be given parenterally, which renders them inconvenient for long-term use. Vitamin K antagonists, such as warfarin, are administered orally, but produce a variable anticoagulant response because genetic polymorphisms, dietary vitamin K intake and multiple drug-drug interactions affect their metabolism. Consequently, coagulation monitoring and frequent dose adjustments are needed to ensure that a therapeutic level of anticoagulation is achieved. This is burdensome for patients and physicians, and costly for the healthcare system. These limitations have prompted the development of new oral anticoagulants that target thrombin or factor Xa and can be given in fixed doses without coagulation monitoring. This paper focuses on the new oral anticoagulants in the most advanced stages of development.
Keywords: Anticoagulants; arterial thromboembolism; direct factor Xa inhibitors; direct thrombin inhibitors, venous thromboembolism